2018
DOI: 10.1093/sleep/zsy171
|View full text |Cite
|
Sign up to set email alerts
|

Effect of adenotonsillectomy for childhood obstructive sleep apnea on nocturnal heart rate patterns

Abstract: Adenotonsillectomy reduces monotonous heart rate patterns throughout quiet event-free sleep, reflecting a reduction in cardiac autonomic modulation. Heart rate pattern analysis may help quantifying the effect of OSAS on autonomic nervous system activity in children. Clinical Trial Registration: The study was registered at Clinicaltrials.gov (#NCT00560859).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 35 publications
(47 reference statements)
0
3
0
1
Order By: Relevance
“…Too high or low variability may be pathologic, while children with OSA have lower HRV. Liu et al demonstrated a greater reduction in monotonous increases or decreases in heart rate in the eAT group, suggesting its positive association with autonomic cardiovascular control.…”
Section: Observations and Discussionmentioning
confidence: 94%
“…Too high or low variability may be pathologic, while children with OSA have lower HRV. Liu et al demonstrated a greater reduction in monotonous increases or decreases in heart rate in the eAT group, suggesting its positive association with autonomic cardiovascular control.…”
Section: Observations and Discussionmentioning
confidence: 94%
“…Obstructive sleep apnea has a detrimental impact on health sequelae such as cognitive behavioural deficits, growth retardation, and CVD, particularly in untreated childhood OSA (Beebe, 2006;Ehsan et al, 2017;Gozal, 2008). Abnormal autonomic control has been reported in children with OSA (Aljadeff et al, 1997;Liu et al, 2018;Martín-Montero et al, 2023;Teo & Mitchell, 2013). A crosssectional case-control study showed that compared to non-OSA controls, children with OSA showed a larger pharyngeal compliance associated with an increased AHI, possibly as consequence of decreased sympathetic tone (reduced LF and LF/HF) in NREM sleep but decreased parasympathetic tone (reduced HF) in REM sleep (Bokov et al, 2021).…”
Section: Upper Airway Surgical Proceduresmentioning
confidence: 99%
“…Berbagai penelitian sebelumnya telah mengkaji pendidikan seks pada anak antara lain: Mukti (2016), Rusydi (2012), Maulana (2018), Hakiki (2015), Liu X, (2018), Solihin (2015), Jatmikowati, dkk (2015) dan Tirtawinata (2016). Beberapa penelitian terdahulu tersebut menyebutkan bahwa terjadinya kejahatan seksual dan penyimpangan prilaku seks sebagai akibat kurangnya pendidikan seks yang benar yang diterima anak sejak dini dalam keluarga dan sekolah.…”
Section: Pendahuluanunclassified